2017
DOI: 10.1016/j.celrep.2017.11.083
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Prerequisites for Diminished Cold Sensitivity in Ground Squirrels and Hamsters

Abstract: Summary Thirteen-lined ground squirrels and Syrian hamsters are known for their ability to withstand cold during hibernation. We found that hibernators exhibit cold tolerance even in the active state. Imaging and electrophysiology of squirrel somatosensory neurons reveal a decrease in cold sensitivity of TRPM8-expressing cells. Characterization of squirrel and hamster TRPM8 showed that the channels are chemically-activated, but exhibit poor activation by cold. Cold sensitivity can be re-introduced into squirre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 32 publications
4
74
1
Order By: Relevance
“…These processes are energetically expensive, underscoring the notion that torpor is an active physiological process that requires molecular fine-tuning. Indeed, recent studies in hibernating rodents revealed profound genomically encoded changes in temperature sensors, mitochondrial function, protein control machineries, and cytoskeletal integrity [5, 6, 33]. We suggest the existence of other such modifications in various groups of enzymes, ion channels, and transporters implicated in energy homeostasis and ionic balance regulation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These processes are energetically expensive, underscoring the notion that torpor is an active physiological process that requires molecular fine-tuning. Indeed, recent studies in hibernating rodents revealed profound genomically encoded changes in temperature sensors, mitochondrial function, protein control machineries, and cytoskeletal integrity [5, 6, 33]. We suggest the existence of other such modifications in various groups of enzymes, ion channels, and transporters implicated in energy homeostasis and ionic balance regulation.…”
Section: Discussionmentioning
confidence: 78%
“…We focused on thermoreceptors and nociceptors, which in squirrels and other rodents have a soma diameter of less than 30 mm (Figure 1B) [46]. To preserve state-specific properties, neurons were incubated at their respective physiological temperatures (37 C for active and 10 C for torpid neurons) prior to patch-clamp recordings at 20 C, the most commonly used temperature for electrophysiological recordings from DRG.…”
Section: Resultsmentioning
confidence: 99%
“…Woolly mammoths (Mammuthus primigenius), in contrast, lived in the extreme cold of the mammoth-steppe where average winter temperatures ranged from −30° to −50°C (MacDonald et al, 2012). Cold adapted and artic species have evolved molecular and physiological adaptations to their circadian systems (Bloch et al, 2013;Lu et al), adipose biology (Fumagalli et al, 2015;Nelson et al, 2014;Welch et al, 2014), and temperature sensation (Matos-Cruz et al, 2017) to deal with serve cold and long periods of persistent dark in winter and light in summer, suggesting mammoths may have also evolved similar adaptations. While temperature sensation in mammals is a complex sensory process in which temperature-sensitive primary sensory neurons convey thermal information from the skin and peripheral organs to the CNS (Vriens et al, 2014), temperature-sensitive transient receptor potential (thermoTRP) cation channels are the major molecular thermosensors (MacDonald et al, 2012;Vriens et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Golden hamsters (Mesocricetus auratus) have TRPM8 channels with dramatically reduced cold sensitivity and do not avoid cold temperatures (Bloch et al, 2013;Lu et al;Matos-Cruz et al, 2017). TRPM8 is also activated in response to cold temperatures and ligands that induce cooling sensations such as menthol, eucalyptol, and the 'super-cooling' agent icilin in heterologous expression systems (Fumagalli et al, 2015;Nelson et al, 2014;Vriens et al, 2014;Welch et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation